P87 A process evaluation of the implementation of assist in scotland. (2nd September 2017) - Dobbie, F; Bauld, L; Purves, R; McKell, J; Dougall, N; White, J; Campbell, R; Amos, A; Moore, L
Abstract : Background: ASSSIT (A Stop Smoking in Schools Trial) is a peer led smoking prevention programme that encourages the dissemination of non-smoking norms. Students (aged 11–13) are nominated by their peers to become peer supporters. ASSIST is an evidence based programme with results from a large cluster randomised trial showing a reduction in smoking prevalence. However, these findings are now 13 years out of date and adolescent smoking prevalence has continued to decline. In 2014 ASSIST was piloted in Scotland. This presentation will present key findings from the Scottish evaluation offering points for consideration for the future delivery of ASSIST and further research areas. Methods: Mixed method study with a range of stakeholders using qualitative (school staff, trainers, students, policy and commissioning leads n=101) and quantitative methods (a before and after student survey across 20 secondary schools in Scotland (n=2166, at follow-up). Results: Feedback was overwhelmingly positive regarding the wider benefits of taking part in ASSIST for peer supporters (i.e. personal and communication skills) but also for the school and communities. Findings showed less certainty regarding the extent of message diffusion and any impact this may have had on adolescent smoking. Student survey results showed no significant change in self-reported smoking prevalence with 1.6% of pupils (n=33) reporting that they smoked one or more cigarettes per week increasing slightly to 1.8% (n=38) at follow-up. The student survey also indicated that conversation recall was low at 9% (n=145) Conclusion: ASSIST is a well delivered, popular programme with additional benefit for students, their wider social network, school and community. Yet, there is uncertainty regarding the extent of message diffusion. Further research is needed to update the existing evidence base.